THE EFFECT OF MURABAHA FINANCING, PROFIT SHARING FINANCING, INTELLECTUAL CAPITAL, AND NON PERFORMING FINANCING (NPF) ON FINANCIAL PERFORMANCE - Siti Nur Azizah; Septiana Mukaromah (Jurnal Reviu Akuntansi dan Keuangan, 2020)
The result was aimed to prove it empirically the effect of financing murabahah, profit sharing financing, intellectual capital, and Non Performing Financing (NPF) on financial performance. The sample in this study was registered sharia banking at the Financial Services Authority for the 2014-2018 period. Data collection techniques in this study used purposive sampling. Methods of analysis of the data used analysis of regression linear multiple. The result of the study financing murabahah have positive significant on financial performance, profit sharing has not effect on financial performance. Capital Employed (B_VACA) and Non Performing Financing (NPF) have a negative effect on financial performance. While Human Capital (iB_VAHU) and Structural Capital (iB_STVA) have not effect on financial performance.